THE STATE OF ENZYMATIC SYSTEMS FOR CARBOHYDRATE HYDROLYSIS IN THE PATHOLOGY OF VISCERAL ORGANS - Sardorbek R. Adizov; Maxmudjon M. Usmonov; Muxamedjan Axmedov; Azizbek F.Valijonov; Askarali A.Kurbonkulov (Scholar Express Journals, 2024)
The study of the morpho-functional state of various parts of the digestivetransport conveyor in the pathology of the visceral organs, which is now so widespread in various countries of the world, has not only theoretical, but also applied significance.
Keywords: Liver; carbohydrases; hydrolysis system